Hermite Wavelet Method for Fractional Delay Differential Equations. (2nd July 2014) - Saeed, Umer; ur Rehman, Mujeeb
Abstract : We proposed a method by utilizing method of steps and Hermite wavelet method, for solving the fractional delay differential equations. This technique first converts the fractional delay differential equation to a fractional nondelay differential equation and then applies the Hermite wavelet method on the obtained fractional nondelay differential equation to find the solution. Several numerical examples are solved to show the applicability of the proposed method.